Determination of butyltin compounds in fish and mussel samples at trace levels by vortex assisted dispersive liquid-liquid microextraction-gas chromatography mass spectrometry - Erarpat, Sezin; Bodur, Suleyman; Oz, Ersoy; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
An accurate and precise analytical method for the determination of monobutyltin (MBT), dibutyltin (DBT) and tributyltin (TBT) compounds has been proposed in this study. Dispersive liquid-liquid microextraction (DLLME) was used to isolate and preconcentrate the analytes from the sample matrix. Some parameters such as type of extraction solvent, type of dispersive solvent, volume of buffer solution, mixing period and derivatization period were optimized with a univariate approach. The optimum amounts of extraction solvent, dispersive solvent and derivatizing agent were determined by a Box-Behnken Design (BED) experiment. To assess the significance of experimental parameters and their interactions, experimented results of all analyte were evaluated with analysis of variance (ANOVA). The optimum DLLME-GC-MS method was validated by analytical figures of merit and the limits of detection for MBT, DBT and TBT were calculated as 0.4, 0.6 and 0.5 mu g/kg, respectively. The optimum method was applied to four aquatic samples including two different fish and mussel samples. The selected organotin compounds were not detected in four samples. Percent recovery results for fish and mussel samples were found to be 84.2-89.5% and 94.9-112.6%, respectively.
Keywords: Butyltin compounds; Food analysis; Food composition; Dispersive liquid-liquid microextraction; Gas chromatography-mass spectrometry; SOLID-PHASE MICROEXTRACTION; ORGANOTIN COMPOUNDS; DERIVATIZATION METHODS; SPECIATION ANALYSIS; PHENYLTIN COMPOUNDS; TIN COMPOUNDS; WATER; TRIBUTYLTIN; ENVIRONMENT; SEDIMENTS; Chemistry; Food Science & Technology